Thermal Stabilisation of Poly(vinyl Chloride) by Organotin Compounds - Arkış, Esen; Balköse, Devrim; Arkış, Esen; Balköse, Devrim (Elsevier Ltd., 2005)
The effect of LSN 117 (dioctyl tin bis isooctyl thioglycollate, an organotin compound) on the heat stability of plasticised PVC was investigated in this study. The organotin stabiliser had carbonyl and carboxylate groups and PVC contained traces of Fe, Zn, Ca, Cu and Sn. The heat stability of the films were tested at 140 °C and 160 °C or 180 °C by heating in an air circulation oven up to 2 h and by measuring HCl evolved using a Metrohm 763 PVC thermomat and by thermogravimetric analysis. The onset of HCl evolution was at 14.3 and 2.5 h at 140 °C and 160 °C, respectively, for PVC film without LSN117. On the other hand, the film with LSN117 did not evolve HCl in 30.3 h at 140 °C. HCl started to evolve from the films with LSN 117 in 14.3 h at 160 °C. The TGA curve also indicated PVC film with LSN 117 degraded at higher temperatures than control films. LSN 117 was found to be a good heat stabiliser for plasticised PVC and it did not have any detrimental effect on mechanical properties.
Keywords: Chemical bonds; Dehydrochlorination; Dioctyl phthalate; Organotin; PVC heat stabilizer